Pre-Session Satiation as a Treatment for Stereotypy During Group Activities. (May 2014) - Rispoli, Mandy; Camargo, Síglia Hoher; Neely, Leslie; Gerow, Stephanie; Lang, Russell; Goodwyn, Fara; Ninci, Jennifer
Individuals with developmental disabilities may engage in automatically reinforced behaviors that may interfere with learning opportunities. Manipulation of motivating operations has been shown to reduce automatically maintained behavior in some individuals. Considering behavioral indicators of satiation may assist in identifying the point at which an abolishing operation has begun to effect behavior. The purpose of this study was to evaluate the effects of pre-session satiation of automatic reinforcement on subsequent levels of stereotypy and activity engagement during group activities for three males ages 5 to 13 years with developmental disabilities. Following functional analyses with analogue conditions, an alternating treatment design compared a pre-session access to stereotypy condition with a no-pre-session access condition prior to group activity sessions. Results indicated that pre-session satiation of the putative reinforcer produced by stereotypy was effective in decreasing stereotypy and increasing activity engagement during subsequent group activities for all participants. These findings add to the literature supporting the effectiveness of abolishing operations to decrease automatically maintained stereotypy.